The Impact of the Rape/Sexual Assault Statutory Aggravating Factor on Death Sentencing Decision Making in Capital Murder Trials in North Carolina (1977–2009): a Propensity Score Matching Approach - Jennings, Wesley G. (Women & criminal justice, 2017)
It was not too many decades ago that rape was a crime for which the death penalty was a permissible punishment in the United States, particularly in death penalty states in the South. Relatedly, historical and contemporary death penalty research almost always focuses on the role of the race of the defendant and, more recently, the race of the victim and defendant-victim racial dyads as being relevant factors in death penalty decision making. As such, the current study employs data from official court records for the population of capital trials (n = 954) in the state of North Carolina (1977-2009) to evaluate the effect of the rape/sexual assault statutory aggravating factor on jurors’ decision to recommend the death penalty. Results suggest that cases in which rape is an aggravating factor had a significantly greater odds of receiving a death penalty recommendation, and these results are robust after also considering the independent effects of defendant-victim racial dyads, even following the application of propensity score matching to equate cases on a host of defendant and victim characteristics, legal and extralegal confounders, and case characteristics. Study limitations and implications are discussed.